ANTISIPASI CEGAH STUNTING UNTUK MEWUJUDKAN GENERASI EMAS 2045 BERSAMA KLINIK AKBAR MEDIKA DAN BKKBN KAB MOJOKERTO - NURHAYATI, NUNUK; Meilinawati, Elies; Partina (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
The Golden Generation 2045 is a discourse and idea in order to prepare the young generation of Indonesia who are qualified, competent and highly competitive. Stunting is malnutrition in babies in the first 1000 days of life that lasts a long time and causes delays in brain development and child growth and development. Due to chronic malnutrition, stunted babies grow shorter than the standard height of toddlers their age. The stunting rate in the world in 2017 was 22.2% or 150.8 million children under 5 years of age. According to WHO, the average stunting rate in Indonesia in 2017 was 36.4%, ranking third in Southeast Asia after Timor Leste and India. According to data from the Indonesian Nutritional Status Survey (SSGI) in 2022, the prevalence of stunting in Indonesia is 21.6%, in East Java it is 19.2% because the number of children under five in East Java is quite high. We carry out community service by collaborating and actively participating with the Mojokerto Regency BKKBN program and the Mojokerto Akbar Medika Clinic using the PAR (Participatory Action Research) method, which is a form of research or community service that involves all relevant parties/stakeholders, which results This PAR method is a necessity to get the desired changes. The PAR method in community service has several stages, including: observation, program preparation, socialization and implementation of work programs, and evaluation of activities. The smallest level of society, namely the family, must receive strengthening regarding stunting in the form of an understanding of stunting and the family must also play an active role in reducing the prevalence rate of stunting by maintaining nutrition for pregnant women and nutrition for toddlers.